Treatment of Exercise Addiction: The current State of Knowledge - Janowiak, Julia; Lenart, Julia; Górowska, Anna; Sobiś, Martyna; Wadowska, Zuzanna; Kiersznowska, Nina; Bogacka, Anna; Janik, Natalia; Buchman, Małgorzata; Miłek, Barbara (Quality in Sport, 2025)
Background: The concept of exercise addiction is commonly understood as a repetitive behavior involving compulsive physical activity despite negative physical, psychological, or social consequences. There are several promising treatment options, including psychological, behavioral, and pharmacological approaches. Aim: This review aims to summarize and evaluate the current state of knowledge on the treatment of exercise addiction, with a particular focus on psychological and behavioral approaches and new potential therapeutic methods. Material and methods: A literature review was conducted using databases including PubMed and Google Scholar. The review examined studies, case reports, and theoretical frameworks on the classification, comorbidities, and treatment of exercise addiction, with a particular focus on cognitive-behavioral therapy, mindfulness-based interventions, and treatment methods adapted from other behavioral addictions. Results: The results indicate that cognitive-behavioral therapy is the primary recommended intervention for exercise addiction. Rational-behavioral therapy and mindfulness-based approaches appear beneficial; however, further research is needed. A single case report described the use of quetiapine, with promising but isolated results. Treatment remains complicated due to comorbid disorders such as eating disorders, anxiety, and depression, all of which require concurrent management. Conclusions: Despite growing interest in exercise addiction, current evidence remains limited due to unclear diagnostic criteria, the homogeneity of study populations, and a lack of data on long-term outcomes. Future research should focus on clearly defining exercise addiction, conducting high-quality clinical trials on randomized groups, and evaluating the long-term effectiveness of therapies.